Viability of Lactobacillus acidophilus LA-5 and Bifidobacterium bifidum BB-12 in Rice Pudding - Tulay Ozcan; Lutfiye Yilmaz-Ersan; Arzu Akpinar-Bayizit; Oya Irmak Sahin; Pinar Aydinol (Mljekarstvo, 2010)
The purpose of this study was to determine the survival of two probiotic micro-organisms (Lactobacillus acidophilus LA-5 and Bifidobacterium bifidum BB-12) in a rice pudding, the impact of these bacteria on hygienic quality, and to verify the perspectives of the product with regard to consumer sensorial acceptance. The products were monitored for the microbial population, pH, titratable acidity and consistency, during storage at 4±1 °C for up to 21 days. Sensory preference was also tested. Even though the viability of the probiotic bacteria was reduced over 21 days of storage, the viable cell concentrations were still sufficient to obtain the desired therapeutic impact. The counts of yeasts-moulds and Staphylococcus spp. decreased in samples with added probiotic bacteria. The sensorial properties of probiotic rice pudding demonstrated similar acceptability to the control up to 14 days and declined thereafter. Rice pudding was considered suitable food for the delivery of probiotic micro-organisms, with sufficient viability and acceptable sensory characteristics.